Looking Deeper at the Reform of New Zealand's Roading System: Driven by Economic Rationalism or an Example of Public Choice Theory in Action - Coull, Matthew J (Victoria University of Wellington Law Review, 2000)
Successive New Zealand governments have investigated reforming New Zealand's road network since 1994. The draft Roads Bill 1998 creates a system of road provision operated according to commercial principles. Roads remain publicly owned, but operational management passes from Transit and 74 territorial authorities to newly incorporated "public road companies". The reforms are examined from "a law and economics" perspective, which finds that while efficiency gains may be generated, the proposed institutional design may prevent these gains from being realised to the proposed extent. The reform proposal is then analysed using public choice theory. This analysis finds that while some elements of the proposal are consistent with legislator and bureaucrat self interest, it contains too many politically sensitive variables to displace the Government's stated "efficiency gains" premise as the overriding motivation for reform.